Integrating Edutainment Media and “Nderek Langit” Local Wisdom to Improve Engagement and Motivation in Solar System Learning for Disabled Students - Anindita Ruhana Dewi; Siska Desy Fatmayanti; Nur Ngazizah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
The problem in Special Schools (SLB) is students’ low understanding of Solar System concepts, resulting in low engagement and motivation. This study aims to develop and implement Solar System learning media based on edutainment and local wisdom for grade VI students with disabilities at Private SDLB Purworejo. A descriptive qualitative case study involved 11 students with mild disabilities. Data were collected through participatory observation, in-depth interviews, and learning documentation, and analyzed using thematic analysis to identify patterns in concept understanding, student involvement, and integration of “Nderek Langit” local wisdom. Findings indicate that edutainment-based media with colorful planet visuals and hands-on activities increased students’ enthusiasm and active participation. Integrating “Nderek Langit” helped students relate abstract Solar System concepts to cultural experiences, such as using moon phases to determine planting times. Students who were usually passive became more responsive and could recognize planet names through visuals and games. Focus duration increased from 3–5 minutes to 15 minutes, accompanied by more positive social interaction. This media effectively enhances understanding of science concepts, engagement, and learning motivation for students with disabilities, and demonstrates potential as an interactive learning innovation rooted in local culture.